2022
DOI: 10.1186/s12935-022-02774-w
|View full text |Cite
|
Sign up to set email alerts
|

Modifying oncolytic virotherapy to overcome the barrier of the hypoxic tumor microenvironment. Where do we stand?

Abstract: Viruses are completely dependent on host cell machinery for their reproduction. As a result, factors that influence the state of cells, such as signaling pathways and gene expression, could determine the outcome of viral pathogenicity. One of the important factors influencing cells or the outcome of viral infection is the level of oxygen. Recently, oncolytic virotherapy has attracted attention as a promising approach to improving cancer treatment. However, it was shown that tumor cells are mostly less oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 90 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…The tumor microenvironment is complex and the core (center) of tumor is less oxygenated and more acidic. It seems that 3D models can mimic these condition and affect the HSV-1 replication and induce resistance to virotherapy, consequently (30). In silico analysis recently has shown the networks of differentially expression genes as potential hypoxia biomarkers which may affect the oncolytic virus replication too (Shayan et al, in-press).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment is complex and the core (center) of tumor is less oxygenated and more acidic. It seems that 3D models can mimic these condition and affect the HSV-1 replication and induce resistance to virotherapy, consequently (30). In silico analysis recently has shown the networks of differentially expression genes as potential hypoxia biomarkers which may affect the oncolytic virus replication too (Shayan et al, in-press).…”
Section: Discussionmentioning
confidence: 99%
“…However, Miska et al found that the deficiency of HIF-1a in Tregs can actually enhance their immunosuppressive function and impede the anti-tumor immunity of CD8+ T cells in glioblastoma (Miska et al, 2019). This suggests that in the hypoxic environment of glioma, oncolytic viruses might enhance the immunosuppressive functions of Tregs by eliminating HIF-1a, even though hypoxia could also promote the replication of the virus (Reinblatt et al, 2004;Shayan et al, 2022). Nonetheless, more research is needed to determine the impact of oncolytic virus therapy on Tregs in the context of the hypoxic glioma microenvironment.…”
Section: Other Immunosuppressive Cellsmentioning
confidence: 99%
“…Oncolytic virotherapy is an emerging treatment approach that uses viruses to selectively target and kill cancer cells 8 . However, hypoxia poses a significant challenge to the effectiveness of oncolytic virotherapy because viral replication and spread are hindered in low oxygen environments 9 , 10 . To overcome this barrier, researchers have explored different strategies, such as using hypoxia-activated prodrugs or modifying viruses to enhance their replication and spread under hypoxic conditions 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%